The blood–brain barriers: novel nanocarriers for central nervous system diseases - Jiajun Liu; Ting Wang; Jian Dong; Yuan Lu (Journal of Nanobiotechnology)
Abstract The central nervous system (CNS) diseases are major contributors to death and disability worldwide. However, the blood–brain barrier (BBB) often prevents drugs intended for CNS diseases from effectively crossing into the brain parenchyma to deliver their therapeutic effects. The blood–brain barrier is a semi-permeable barrier with high selectivity. The BBB primarily manages the transport of substances between the blood and the CNS. To enhance drug delivery for CNS disease treatment, various brain-based drug delivery strategies overcoming the BBB have been developed. Among them, nanoparticles (NPs) have been emphasized due to their multiple excellent properties. This review starts with an overview of the BBB’s anatomical structure and physiological roles, and then explores the mechanisms, both endogenous and exogenous, that facilitate the NP passage across the BBB. The text also delves into how nanoparticles' shape, charge, size, and surface ligands affect their ability to cross the BBB and offers an overview of different nanoparticle classifications. This review concludes with an examination of the current challenges in utilizing nanomaterials for brain drug delivery and discusses corresponding directions for solutions. This review aims to propose innovative diagnostic and therapeutic approaches for CNS diseases and enhance drug design for more effective delivery across the BBB. Graphical abstract